The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s11139-015-9712-x
|View full text |Cite
|
Sign up to set email alerts
|

New hypergeometric connection formulae between Fibonacci and Chebyshev polynomials

Abstract: Abstract. We establish new connection formulae between Fibonacci polynomials and Chebyshev polynomials of the first and second kinds. These formulae are expressed in terms of certain values of hypergeometric functions of the type 2 F 1 . Consequently, we obtain some new expressions for the celebrated Fibonacci numbers and their derivatives sequences. Moreover, we evaluate some definite integrals involving products of Fibonacci and Chebyshev polynomials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 21 publications
(28 reference statements)
1
11
0
Order By: Relevance
“…Remark 3. The two relations in (32) and (33) are in agreement with those recently developed in [13].…”
Section: Connection Formulae Between Two Different Generalized Polyno...supporting
confidence: 90%
See 1 more Smart Citation
“…Remark 3. The two relations in (32) and (33) are in agreement with those recently developed in [13].…”
Section: Connection Formulae Between Two Different Generalized Polyno...supporting
confidence: 90%
“…Due to this importance, the connection problems between various polynomials have been investigated by many authors. In this regard, Abd-Elhameed et al in [13] solved the connection problems between Fibonacci polynomials and Chebyshev polynomials of first and second kinds. Some other studies concerning connection problems can be found in [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies were devoted to solving these problems via different approaches. For some articles interested in investigating these problems, one can be referred for example to [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Several algorithms were described to solve the connection and linearization problems. In most cases, the connection and linearization coefficients are expressed in terms of hypergeometric functions of certain arguments; see, for example [20,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the literature on this subject is vast and a wide variety of methods have been developed using several techniques. Here, we refer mainly to the following references [1,2,3,8,11,24,30,31,49,50,56]. Zeros of orthogonal polynomials is another widely discussed subject due to its applications in several problems of applied sciences [54] and their crucial role in quadrature formulas [22].…”
Section: Introductionmentioning
confidence: 99%